Increased plasma advanced oxidation protein products is an early marker of endothelial dysfunction in type 2 diabetes patients without albuminuria 2 - Liang, Min; Wang, Jun; Xie, Chao; Yang, Yan; Tian, Jian Wei; Xue, Yao Ming; Hou, Fan Fan (Journal of diabetes, 2014)
Endothelial dysfunction is an early event of cardiovascular disease in type 2 diabetes (T2D) and can occur before albuminuria. Oxidative stress has been found to play a key role in the development of endothelial dysfunction. Therefore, we hypothesized that increases in plasma advanced oxidized protein products (AOPPs), a family of oxidized, dityrosine-containing protein compounds generated during oxidative stress, could serve as an early marker of endothelial dysfunction in T2D patients without albuminuria. We conducted a cross-sectional investigation of 147 newly diagnosed T2D patients (112 without albuminuria and 35 with albuminuria) and 49 age-matched healthy control subjects. Flow-mediated vasodilation (FMD) was used to assess endothelium-dependent vasodilator function, and plasma soluble intercellular adhesion molecule-1 (sICAM-1) concentrations were determined to evaluate vascular injury. Plasma AOPPs concentrations were measured using a modified spectrophotometric assay. Plasma AOPPs concentrations were significantly elevated in normoalbuminuric patients with T2D compared with healthy controls. Plasma AOPPs concentrations were correlated with FMD and plasma sICAM-1 concentrations in this population. Multivariate regression analysis demonstrated that increased plasma AOPPs was the strongest risk factor for impaired endothelial vasodilation and increased sICAM-1 in these patients. Similar results were observed in T2D patients with albuminuria. Increased plasma AOPPs concentrations were an independent risk factor for endothelial dysfunction, and therefore may be an early marker of vasculopathy in individuals at an early stage of diabetes.